ANTERIOR GASTRIC DIVISION BY STAPLER AND POSTERIOR TRUNCAL VAGOTOMY IN THE SURGICAL TREATMENT OF CHRONIC DUODENAL ULCER - Settar BOSTANOĞLU; Tevfik KÜÇÜKPINAR; Ayhan KESKİN and Gündüz TUNÇ and Kemal YANDAKÇI (Turkish Journal of Gastroenterology, 2020)
-